Molecular Mechanisms of Endocrine Resistance in Estrogen-Receptor-Positive Breast Cancer - Belachew, Esmael Besufikad; Sewasew, Dareskedar Tsehay (Frontiers in Endocrinology, 2021)
The estrogen receptor is a vital receptor for therapeutic targets in estrogen receptor-positive breast cancer. The main strategy for the treatment of estrogen receptor-positive breast cancers is blocking the estrogen action on estrogen receptors by endocrine therapy but this can be restricted via endocrine resistance. Endocrine resistance occurs due to both de novo and acquired resistance. This review focuses on the mechanisms of the ligand-dependent and ligand-independent pathways and other coregulators, which are responsible for endocrine resistance. It concludes that combinatorial drugs that target different signaling pathways and coregulatory proteins together with endocrine therapy could be a novel therapeutic modality to stop endocrine resistance.